DETERMINANT OF DIVIDEND DISTRIBUTION: Evidence from Indonesia Stock Exchange - Nathania, Nathania; Panggabean, Rosinta Ria (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This research aims to determine the effects of return on investment, operating cash flow, management assets, debt to equity ratio, and firm size on dividends. This research involved 23 companies listed on Indonesia Stock Exchange as the research sample. The sampling technique used was purposive sampling method. The analysis used multiple linear regression with E-Views version 9. The results show that return on investmetnt has an influence on cash dividends, while operating cash flow, management assets, debt to equity ratio and firm size do not have an effect on cash dividends.